1981
DOI: 10.1210/endo-109-6-1841
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aldosterone in the Development of Hypertension in Spontaneously Hypertensive Rats*

Abstract: A continuous sc infusion of aldosterone for 2 weeks (10 micrograms/day) markedly increased the blood pressure of male, adrenalectomized (ADX), spontaneously hypertensive rats (SHR) from 142 to 178 mm Hg, which was similar to the increase seen in a group of sham-operated SHR. The blood pressure in a group of ADX SHR maintained without aldosterone declined from 141 to 119 mm Hg during the 2 weeks after surgery. Wistar Kyoto (WKY) and Sprague-Dawley (SD) rats treated in an identical fashion remained normotensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…8,13,[17][18][19] Finally, in SHR, adrenocortical steroids are required for the development of hypertension, probably via the permissive action of both mineralocorticoid and glucocorticoid activities. 20,21 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,13,[17][18][19] Finally, in SHR, adrenocortical steroids are required for the development of hypertension, probably via the permissive action of both mineralocorticoid and glucocorticoid activities. 20,21 …”
mentioning
confidence: 99%
“…8,13,[17][18][19] Finally, in SHR, adrenocortical steroids are required for the development of hypertension, probably via the permissive action of both mineralocorticoid and glucocorticoid activities. 20,21 In the present study, we examined the contribution of brain MRs in the maintenance of high blood pressure in SHR. For this purpose, we assessed the effect of single ICV administration of the selective MR antagonist RU28318 on cardiovascular and renal functions of normotensive Wistar-Kyoto rats (WKY) and adult SHR that were fed a standard-or high-sodium diet.…”
mentioning
confidence: 99%
“…The narrow and lipid-depleted zonae glomerulosae of the fish protein + 1 % salinefed rats suggests that these animals have been secreting extra quantities of aldosterone, specifically. In this connection, the author 26 and others [27][28][29] have shown that plasma renin levels are low in SHR while circulating aldosterone levels are elevated and treatment of adrenalectomized SHR with aldosterone will restore their high blood pressure.…”
Section: Pathologymentioning
confidence: 96%
“…Similarly, animal models that either lack aldosterone (adrenalectomized Sprague-Dawley rats) or are resistant to aldosterone actions (Wistar-Furth rats) are characterized by resistance to remnant nephropathy [36,[38][39][40][41]. If aldosterone is reinstituted via an infusion, it markedly increases the blood pressure in adrenalectomized spontaneously hypertensive rats [42], induces lesions of malignant nephrosclerosis in the deoxycorticosterone acetate-salt hypertensive rat model [43], and restores proteinuria and glomerulosclerosis in remnant rats treated with losartan and enalapril to an extent similar to that seen in untreated remnant rats [44]. Rocha et al [45•] concluded that spontaneously hypertensive strokeprone rats (SHR-SPs) receiving the aldosterone antagonist, spironolactone, for 3 to 4 weeks had similar blood pressure profiles but fewer nephrosclerotic histologic lesions and less proteinuria than the placebo group.…”
Section: Aldosterone Synthesis and Receptorsmentioning
confidence: 99%